Antiretroviral drug susceptibility of a hinge region variant of HIV-1 subtype C protease - Zondagh, Jake (My University, 2018)
Since their discovery, protease inhibitors continue to be an essential component of antiretroviral treatment for human immunodeficiency virus type 1 (HIV-1). However, the development of resistance to protease inhibitors remains one of the most significant challenges in the fight for sustained viral suppression in those infected with HIV-1. Studies show that specific mutations arising within the HIV-1 gag and protease genes can lead to the development of resistance. In this research, a South African HIV-1 subtype C Gag-protease variant (W1201i) was investigated. This variant was considered due to the presence of a mutation and insertion (N37T↑V), located within the hinge region of the protease enzyme. Moreover, the variant displayed the following polymorphisms: Q7K, I13V, G16E, M36T, D60E, Q61E, I62V and M89L. Genotyping of W1201i Gag revealed a previously unreported MSQAG insertion between the CA/p2 and p2/NC cleavage sites. Additionally, a mutation and insertion (I372L↑M), and multiple polymorphisms (S369N, S371N, I373M and G377S) were discovered within the p2/NC cleavage site. Single-cycle phenotypic assays were performed to determine the drug susceptibility and replication capacity of the variant. The results show that the mutations present in the N37T↑V protease conferred a replicative advantage and reduced susceptibility to lopinavir, atazanavir and darunavir. Interestingly, the mutations in W1201i Gag were found to modulate both replication capacity and protease inhibitor susceptibility. In silico studies were performed to understand the physical basis for the observed variations. Molecular dynamics simulations showed that the N37T↑V protease displayed altered dynamics around the hinge and flap region and highlighted the amino acids responsible for the observed fluctuations. Furthermore, induced fit docking experiments showed that the variant bound the iv protease inhibitors with fewer favourable chemical interactions than the wild-type protease. Collectively, these data elucidate the biophysical basis for the selection of hinge region mutations and insertions by the HI virus and show that protease, as well as Gag, needs to be evaluated during resistance testing.
A thesis submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg in fulfilment of the requirements for the degree of Doctor of Philosophy. Johannesburg, 28 May 2018.
Keywords: Antiretroviral agents; AIDS (Disease)--Treatment--South Africa; HIV infections--Treatment--South Africa; Protease inhibitors